Current state of the accounting outsourcing market in Ukraine (Economics and region, 2023)
The transition of companies to remote working as a result of the COVID-19 pandemic has forced them to use outsourcing companies more frequently to perform certain functions, particularly accounting. As a result of this and numerous advantages of outsourcing for the client, the volume of outsourcing services on the world market has increased. In Ukraine, too, outsourcing relations have gained popularity, which is confirmed by the dynamics of the number of business entities in the field of accounting, the volume of services they provide, and their place in the world ranking. However, due to the lack of necessary knowledge, experience in this field, financial difficulties, the share of accounting outsourcing is much lower than the indicators of developed countries of the world. In the conditions of martial law, almost all indicators of business activity of enterprises in Ukraine decrease: the number of orders, employment of personnel, stocks, volume of production or provision of services, but the share of business entities that have completely or partially stopped their activities as a result of the war is gradually decreasing. Ukrainian business, looking for ways out of the crisis, is ready to invest in export activities. However, this is hindered by: low level of foreign language skills; insufficient knowledge, experience and qualified personnel in this field; difficulties in finding orders, partners; insufficient awareness of foreign markets; non-compliance of products/services with international requirements; financial and logistical problems; lack of experience in international sales and marketing, etc. In order to overcome these obstacles, specialists from outsourcing companies who are familiar with the peculiarities of organising export activities are brought in. The cost of their services is lower than the wages of full-time employees, which is a valid argument in times of war. These factors, together with the advantages of accounting outsourcing, contribute to its development in Ukraine under modern conditions. However, in order to reach the level of outsourcing services of the developed countries of the world, it is necessary to implement electronic document flow, domestic accounting information technologies and create a legislative framework for regulating outsourcing relations.
Keywords: outsourcing; accounting; development; current state; prospects